Strategi Apresiasi Seni Pada Pembelajaran School Visit di Masa Pandemi - Alfian Eko Widodo Adi Prasetyo (Lembaga Sosial Rumah Indonesia, 2021)
Learning carried out in the midst of the Covid 19 pandemic has many obstacles in the implementation process, especially for early childhood. Learning that is done online is now trying to be applied to AUD education in schools. Educators try to provide solutions to deal with learning in the midst of a pandemic. One of them is the application of School Visits and appreciative learning. This study aims (1) to determine the results of the application of the School Visit learning method (2) to determine the learning process of art appreciation given to students. The research method used is qualitative. With observation data collection techniques, interviews, and study of learning documents. The subjects of this research are educators and parents of AZ-ZAHRA ISLAMIC Kindergarten students. The results showed that the School Visit learning model was able to build a child's learning stimulus. Meanwhile, learning using art appreciation forms can encourage children to be more attractive and creative in learning. The learning techniques applied to the School Visit model make it easier for teachers, students and parents to catch up and communicate material in the midst of a pandemic. The supporting factors for the School Visit learning process and art appreciation are educators, student characteristics, goals, situations and infrastructure that support the learning process in the midst of a pandemic.